Theoretical Basis of Methods of Measurement and Functioning of the Shadow Economy - Suyun Artikovich, Abdullaev; Kahramon Kurbandurdievich, Mambetjanov (International Journal of Psychosocial Rehabilitation, 2020)
This article covers the concepts of "Shadow Economy," types, mechanisms, branches, and spheres of its implementation. The main problems in the calculation of the share of the shadow economy as a part of GDP and ways to eliminate these problems are given. As well as scientific proposals and practical recommendations on improving the methods of computing the shadow economy as part of GDP.